Literacy among tobacco users and healthcare professionals about tobacco harm reduction strategies: a scoping review protocol - Iqbal, Sajid; Patwardhan, Sudhanshu; Sivarajan Froelicher, Erika; Asmat, Kainat; Barolia, Rubina (Frontiers in Public Health, 2025)
ObjectiveThe proposed review identifies and describes the extent of Tobacco Harm Reduction (THR) strategies in Pakistan. It also examines the awareness and understanding of these strategies among healthcare professionals and tobacco users in Pakistan.IntroductionTobacco consumption poses a significant threat to human health and is a leading cause of non-communicable diseases. Over the last two decades, the prevalence of tobacco use has increased in low-and middle-income countries (LMICs), which has considerably contributed to the increasing prevalence of Non-Communicable Diseases (NCDs). Tobacco is consumed in various forms, including manufactured cigarettes, hookah/shisha, chewing tobacco, and dipping tobacco. Tobacco use can be reduced and prevented through various strategies adopted by many countries worldwide. One prominent strategy is THR. THR involves the use of safer nicotine products in recommended doses to cope with the symptoms of withdrawal and increase tobacco users’ chances of quitting smoking. In Pakistan, the concept of tobacco harm reduction (THR) is not widely recognized by healthcare professionals and tobacco users.Inclusion and exclusion criteriaLiterature available on Pakistani adults and adolescents (aged 13 years and above) will be included. Literature available as free full text will be included regardless of the publication date. Furthermore, literature available in English or Urdu will be considered eligible. Also, literature available in any form of publication, such as research studies, reviews, organizational websites or blogs, will be considered eligible. Literature that includes Pakistani data mixed with data from any other country will be excluded.MethodsThe literature search will use PubMed, CINAHL, ProQuest Theses & Dissertations, EBSCO Dentistry and Oral Sciences, and PsycInfo databases for online and gray literature. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram will record the included and excluded literature. Two independent reviewers will screen all the retrieved literature. After confirming the eligibility criteria, data from included records will be extracted on an Excel sheet that will record the important characteristics of the literature source and the main findings. Meta-synthesis of collated data will be performed, and the results will be presented as narrative summaries and frequency tables.Systematic review registrationhttps://osf.io/dashboard.